2022
DOI: 10.1177/11206721221078678
|View full text |Cite
|
Sign up to set email alerts
|

Neovascular Glaucoma in Children: A case series and a review of the literature

Abstract: Purpose To study the uncommon causes and treatment options for neovascular glaucoma in children. Patients and Methods A review of the literature on neovascular glaucoma in children was conducted and we present three cases of neovascular glaucoma in children. Results We present three cases of neovascular glaucoma: two cases were secondary to a retinal vasoproliferative tumor—one to neurofibromatosis type 1 and the other to exudative retinopathy secondary to mild retinopathy of prematurity—and one case was secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Overall, reported risk factors include: APLA, [15][16][17][18][19] homocysteinemia, platelet over-responsiveness, 9,20 vasculitis, acute infections, inflammatory states, and optic pathway tumors. 3,11,[21][22][23][24][25][26][27] In some reports, more than one genetic abnormality was found in patients with RVO, suggesting synergistic interactions that may increase the risk. 28 As for SOVT cases, infectious etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, reported risk factors include: APLA, [15][16][17][18][19] homocysteinemia, platelet over-responsiveness, 9,20 vasculitis, acute infections, inflammatory states, and optic pathway tumors. 3,11,[21][22][23][24][25][26][27] In some reports, more than one genetic abnormality was found in patients with RVO, suggesting synergistic interactions that may increase the risk. 28 As for SOVT cases, infectious etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Both conditions are extremely rare among children, only 10%–15% of RVO patients are younger than 40 years 1,2 . The commonest presentation is sudden, unilateral, painless loss of vision 3,4 . RVO diagnosis relays on ophthalmic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic causes include neurofibromatosis type 1, von Hippel-Lindau syndrome, systemic lupus erythematosus, and ocular metastases. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) and diabetic iridopathy (DI) are ophthalmic microvascular complications of diabetes. Under the circumstances of poorly controlled blood glucose or long diabetes duration, DI can progress into neovascular glaucoma (NVG), which is a serious vision-threatening neovascular sequela [1,2]. Previous studies of diabetic patients by iris fluorescein angiography revealed that dye leakage was present at the pupillary margin among diabetic patients without DR or DI, indicating that the abnormality in iris vasculature precedes that in retina circulation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%